Mesenchymal Stem Cells Recruit CCR2(+) Monocytes to Suppress Allergic Airway Inflammation - Takeda, Katsuyuki (J Immunol, 2018)
Mesenchymal stem cells (MSC) exert immune modulatory properties and previous studies demonstrated suppressive effects of MSC treatment in animal models of allergic airway inflammation. However, the underlying mechanisms have not been fully elucidated. We studied the role of MSC in immune activation and subsequent recruitment of monocytes in suppressing airway hyperresponsiveness and airway inflammation using a mouse model of allergic airway inflammation. MSC administration prior to or after allergen challenge inhibited the development of airway inflammation in allergen-sensitized mice. This was accompanied by an influx of CCR2-positive monocytes, which were localized around injected MSC in the lungs. Notably, IL-10-producing monocytes and/or macrophages were also increased in the lungs. Systemic administration of liposomal clodronate or a CCR2 antagonist significantly prevented the suppressive effects of MSC. Activation of MSC by IFN-γ leading to the upregulation of CCL2 expression was essential for the suppressive effects, as administration of wild-type (WT) MSC into IFN-γ–deficient recipients, or IFN-γ receptor- or CCL2-deficient MSC into WT mice failed to suppress airway inflammation. These results suggest that MSC activation by IFN-γ, followed by increased expression of CCL2 and recruitment of monocytes to the lungs, is essential for suppression by MSC in allergen-induced airway hyperresponsiveness and airway inflammation.